Evaluation of oral health attitude and behavior among a group of dental students in Puducherry, India: A preliminary cross-sectional study - Jananni Muthu; Gayathri Priyadarshini; Sivaramakrishnan Muthanandam; Saravanakumar Ravichndran; Pratebha Balu (Wolters Kluwer Medknow Publications, 2015)
Context: Oral behavior reflects individual perception on oral health. Behavior and attitude of oral health providers, especially dentists, towards oral health affect their capacity to deliver oral health care services. This attitude plays a important role in determining the oral health condition of population. Aim: The purpose of this study is to evaluate the oral health attitude and behavior among a group of dental students in India and to find any gender-based differences in terms of oral health attitude and behavior. Materials and Methods: A total of 282 dental students of Indira Gandhi Institute of Dental Sciences, SBV University, Puducherry, India participated in the study. A simplified English version of Hiroshima University Dental-Behavioral Inventory (HU-DBI) was adopted. Statistical Analysis Used: SSP version 2.80 software was used to analyze the data. Chi-square test was used to find the differences in the distribution of "yes" among students from the different academic year as well as between male and female students. Statistical significance was set at P ≤ 0.05. Results: Statistical significance was observed for the responses between the students from different academic years brushing frequency, careful brushing of teeth, using brush with hard bristles, careful self-evaluation of brushing and satisfied appearance of teeth and gums. Male students preferred to use a tooth brush with hard bristles and regular mouth washes than female students. With regards to worrying about bad breath, male students had more "yes" responses than females. Conclusions: Oral health attitude and behavior increased with the increasing levels of dental education, and no significant differences were observed among male and female dental students.